Heme regulation in mouse mammary carcinoma and liver of tumor bearing mice-I. Effect of allyl-isopropylacetamide and veronal on δ -aminolevulinate synthetase, cytochrome P-450 and cytochrome oxidase - Navone, N.M. (1990)
1. 1. Basal levels and allyl-isopropylacetamide (AIA) or veronal induced levels of δ-aminolevulinate synthetase (ALA-S), cytochrome P-450 (cyt P-450) and cytochrome oxidase were determined in tumor (T) and liver of both normal mice (NM) and T bearing mice (TBM). 2. 2. Basal levels of ALA-S were nearly the same in either source. The amount of cyt P-450 was lower in TBM liver than in NM liver, and no detectable in T. While the basal activity of cytochrome oxidase in TBM liver and T were higher than those of NM liver. 3. 3. In AIA intoxicated animals there was a lower induction of ALA-S in liver of TBM than in NM liver. There was no induction in T ALA-S. The loss of cyt P-450 was less in TBM liver when compared with NM liver. 4. 4. The induction level of cyt P-450 after veronal administration was nearly the same in liver of both TBM and NM. 5. 5. We conclude that lower induction of liver ALA-S activity in TBM liver is due to correspondingly lower drug metabolism ability of TBM liver. Otherwise our results suggest that the control mechanism operating in T and probably in its original tissue are different from those described for normal liver. © 1990.